PROVIDING LOAN FUNDS FOR PRIMKOPPOL MEMBERS USING THE SAW METHOD - Ramadhan Pratama Putra Hasibuan; Bachtiar Efendi; Suci Andriyani (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The provision of loan funds is one of the important activities in improving the welfare of Primkoppol members (Police Cooperative). The process of determining the eligibility for loan disbursement in PRIMKOPPOL POLRES Asahan is still lacking systematic timing delays in making decisions in managing the disbursement of loan funds. Therefore, an efficient and effective method is needed to minimize risks and maximize profits for the cooperative and its members. One method that can be used is the Simple Additive Weighting (SAW) method, which has been proven effective in various decision-making contexts. This study aims to apply the SAW method in the process of disbursing loan funds for Primkoppol members, and to evaluate the performance of this method in selecting eligible loan recipients and optimizing fund allocation. The loan disbursement process uses the SAW method, which calculates the relative preference value for each prospective loan recipient based on predetermined criteria. The results of this study indicate that by applying the Simple Additive Weighting method to 10 loan applicants, 3 applicants successfully applied for loans with a preference value > 0.7, in line with the requirements. The implementation of the SAW method in loan disbursement for Primkoppol members has successfully increased efficiency and accuracy in selecting loan recipients. Keywords : cooperative; decision support systems; simple additive weighting (SAW).  Abstract: Pemberian dana pinjaman merupakan salah satu kegiatan yang penting dalam meningkatkan kesejahteraan anggota Primkoppol (Koperasi Polisi). Proses penentuan kelayakan pemberian pinjaman di PRIMKOPPOL POLRES Asahan masih kurang sistematis keterlambatan waktu dalam menentukan keputusan dalam mengelola pemberian dana pinjaman. Untuk itu diperlukan suatu metode yang efisien dan efektif untuk meminimalkan risiko dan memaksimalkan keuntungan bagi koperasi dan anggotanya. Salah satu metode yang dapat digunakan adalah metode Simple Additive Weighting (SAW), yang telah terbukti efektif dalam berbagai konteks pengambilan keputusan. Penelitian ini bertujuan untuk menerapkan metode SAW dalam proses pemberian dana pinjaman bagi anggota Primkoppol, serta untuk meng-evaluasi kinerja metode tersebut dalam memilih penerima pinjaman yang layak dan meng-optimalkan alokasi dana. Proses pemberian dana pinjaman menggunakan metode SAW yang menghitung nilai preferensi relatif bagi setiap calon penerima pinjaman berdasarkan kriteria yang telah ditetapkan. Hasil dari penelitian ini menunjukan bahwa dengan menerapkan metode Simple Additive Weighting dari 10 calon pemohon pinjaman, 3 calon berhasil mampu mengajukan pinjaman dengan nilai preferensi > 0,7. sesuai dengan persyaratan. Implementasi metode SAW dalam pemberian dana pinjaman bagi anggota Primkoppol berhasil meningkatkan efisiensi dan keakuratan dalam pemilihan penerima pinjaman. Kata Kunci : koperasi; simple additive weighting (SAW); sistem pendukung keputusan.